Anthraquinone in Chinese tea: concentration and health risk assessment - Qianqian Xie; Dingguo Jiang; Ling Yong; Xiao Xiao; Dajin Yang; Haixia Sui; Daoyuan Yang; Tong Ou; Yin Wang; Yan Song (Cogent Food & Agriculture)
Recently, the safety of anthraquinone (AQ) in Chinese tea has received much attention. This study determined the concentration of AQ in 1573 Chinese tea samples by gas chromatography-tandem mass spectrometry (GC-MS/MS). It was observed that the total detection rate of AQ was 60.97%, and the mean concentration was 0.0170 mg/kg. The concentration levels of AQ in tea varied by different types of tea, different packaging types, different sale spots and different tea-producing areas. The results of the deterministic assessment show that the health risks associated with daily exposure to AQ via tea consumption are low in different populations in China. For the general population, the mean daily exposure of AQ via tea consumption was (2.50 × 10−4) µg/kg body weight (BW), 0.0037% of the acceptable daily intake of AQ (6.8 µg/kg BW). In the different sex-age groups, the highest mean daily exposure of AQ via tea consumption was found in the male group aged ≥ 60 years, which was (2.84 × 10−4) µg/kg BW. The high consumer exposure (95th percentile, P95) was found in the female group aged ≥ 60 years, which was (9.36 × 10−4) µg/kg BW. Green tea is the main type of tea with AQ exposure by Chinese tea consumers.